2019
DOI: 10.16965/ijar.2019.268
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on Neck Shaft Angle and Length Femur in South Gujarat

Abstract: The femur is the largest and strongest bone in the body and the structure of its proximal portion allows the leg to move in three dimensions relative to the torso, thus serving as a linchpin of human mobility. Moreover, age related and pediatric disorders at this skeletal site are common and confer strong risk factors for current and future disability. The femur forms the skeleton of the thigh, carries body weight, supports the movements of leg and provides attachment to the muscles. Morphology of bones is ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…As the results of the study of Vaishnani et al 22 in India the femur length was found as 435.8 ± 27.32 mm. Verma et.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…As the results of the study of Vaishnani et al 22 in India the femur length was found as 435.8 ± 27.32 mm. Verma et.…”
Section: Discussionmentioning
confidence: 80%
“…In the study of Mahaisavariya et al21 in Thailand, they found the neck-shaft angle 128.04 o . Vaishnani et al22 studied investigated the neck-shaft angle in India and they found the neck-shaft angle 137.2 ± 5.1 o . İyem et al23 found the neck-shaft angle as 130.4 ± 5.1 o in Turkey.…”
mentioning
confidence: 99%